Exploring national and regional trends in smoking prevalence among women: A systemic review and meta-analysis - Ali Abkr Shok; Hassan Abdullah Najmi; Mohammed Ali Refaey; Fuad Ali Sahli; Attyah Ahmed Aahwas; Yahia Abdullah Maghlat; Abdullah Hassan Abu Ageel; Nawaf Omar Hamzi; Turky Mohammed Kulib Ali; Yahya Hassan Zarban; Abutalib Hassan Zarban (Saudi Journal for Health Sciences)
This study aimed to comprehensively review the global prevalence of both past and current cigarette smoking among women and examine trends over time through a systematic review and meta-analysis. A systematic search was conducted across multiple electronic databases, including PubMed, Web of Science, Scopus, and Ovid, focusing on studies published between January 2019 and March 2024. Eligible studies reported smoking prevalence among women aged 18 years and older, covering regions such as the Americas, Asia, Europe, Africa, and Oceania. Statistical analyses were performed using Stata 16.0, including pooled prevalence estimates, cumulative meta-analysis, and univariate meta-regression to identify sources of heterogeneity. Of the 31,219 studies identified, 26 met the inclusion criteria, representing data from 11,143,238 women. The overall pooled prevalence of ever smoking was 26% (95% confidence interval CI: 24%–32%), while current smoking was 15% (95% CI: 14%–19%). Significant regional variations were found, with the highest prevalence of ever smoking in Europe (37%) and the lowest in Asia (13%). A cumulative meta-analysis revealed a declining trend in smoking prevalence from 2019 to 2024. Meta-regression analysis showed significant effects of study year and continent on smoking prevalence. These findings highlight substantial regional differences and a notable decline in recent years, providing important insights for developing targeted public health interventions and policies to reduce smoking-related health risks among women.